2021
DOI: 10.3389/fcvm.2021.740896
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis Evaluating the Colchicine Therapy in Patients With Coronary Artery Disease

Abstract: Background: Evidence from recent studies has shown the benefits of colchicine for patients with coronary artery disease. The aim was to assess the effect of colchicine treatment on cardiovascular events, with an estimation of the risk of discontinuation and net clinical benefit.Methods and Results: Fourteen trials with a total of 13,186 patients were selected through a systematic search. Colchicine therapy significantly reduced the relative risk of primary endpoint by about 30% [RR 0.70 (95%CI:0.56–0.88)]. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Consistently with these results, the 13 clinical trials by Kofler (2021) [ 32 ] and 14 clinical trials by Grajek (2021) [ 33 ] meta–analyses evaluating the efficacy of colchicine in patients with coronary artery disease found a reduction in MACE of 35 % and 30 %, respectively, relative to placebo, positioning this drug product as one of the therapies of choice in this setting alongside usual medical therapy.…”
Section: Discussionmentioning
confidence: 75%
“…Consistently with these results, the 13 clinical trials by Kofler (2021) [ 32 ] and 14 clinical trials by Grajek (2021) [ 33 ] meta–analyses evaluating the efficacy of colchicine in patients with coronary artery disease found a reduction in MACE of 35 % and 30 %, respectively, relative to placebo, positioning this drug product as one of the therapies of choice in this setting alongside usual medical therapy.…”
Section: Discussionmentioning
confidence: 75%
“…Colchicine is an anti-inflammatory drug widely used to treat gout. Recent literature suggested that low-dose colchicine had cardiovascular benefits in patients with acute coronary syndrome through reducing inflammation ( 33 ). The effect of anti-inflammatory therapy on NOAF after AMI should also be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many conventional pairwise meta-analyses have systematically evaluated and consistently established the effects and safety of colchicine for the treatment of patients with CAD [19][20][21][22][23][24][25][26]63,68,69 ; however, all these findings from previous meta-analyses did not inform practitioners which dosing regimen may be preferred for these patients. Given this open issue, the current network meta-analysis rationally classified colchicine dose into 3 regimens based on published evidence 26 and first determined the comparative efficacy and safety among 3 dosing regimens.…”
Section: The Strengths Of This Network Meta-analysismentioning
confidence: 99%